KORELASI ANTARA TAFSIR DAN TA’WIL : STUDI KOMPREHENSIFTENTANG METODOLOGI PENAFSIRAN AL-QUR’AN - Yoga Agus Yulianto; Hamidullah Mahmud (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The correlation between tafsir and ta’wil in the methodology of Qur'anic interpretation aims to understand how these two approaches complement each other in the process of interpreting the verses of the Qur'an. Tafsir generally focuses on the literal and contextual explanation of Qur'anic verses, while ta’wil delves into deeper, esoteric meanings, particularly in ambiguous (mutashabihat) verses. Using a qualitative approach and literature review, this research analyzes classical and contemporary exegesis to identify how scholars across different eras combine these approaches. The findings reveal that the correlation between tafsir and ta’wil enriches the overall understanding of the Qur'an. Classical scholars tend to separate tafsir and ta’wil methodologically, whereas contemporary scholars often integrate both approaches to address modern challenges, such as social change and interpretative pluralism. This study emphasizes the importance of synergy between tafsir and ta’wil in developing a more comprehensive and relevant method of Qur'anic interpretation in the contemporary era.